2016
DOI: 10.1039/c6cp06088a
|View full text |Cite
|
Sign up to set email alerts
|

Thermal transport properties of antimonene: an ab initio study

Abstract: Searching for low thermal conductivity materials is crucial for thermoelectric devices. Here we report on the phonon transport properties of recently fabricated single layer antimony, antimonene [Ares, et al., Adv. Mater., 2016, 28, 6332]. Ab initio calculations in combination with the Boltzmann transport equation (BTE) for phonons show that antimonene has a low lattice thermal conductivity (15.1 W m K at 300 K), indicating its potential thermoelectric applications. The low lattice thermal conductivity is due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 56 publications
4
35
0
Order By: Relevance
“…However, the out-of-plane acoustic modes are still marked with ZA modes. It is clearly seen that LA and TA branches are linear near the Γ point, while ZA branch deviates from linearity, which shares the general feature of 2D materials [8][9][10][11][12][13][14][15][16][17][18][19][20] . It is clearly seen that both acoustic and optical branches overall move downward from As to SbAs to Sb monolayer, and the widthes of acoustic and optical branches gradually become narrow.…”
Section: Main Calculated Results and Analysismentioning
confidence: 91%
See 1 more Smart Citation
“…However, the out-of-plane acoustic modes are still marked with ZA modes. It is clearly seen that LA and TA branches are linear near the Γ point, while ZA branch deviates from linearity, which shares the general feature of 2D materials [8][9][10][11][12][13][14][15][16][17][18][19][20] . It is clearly seen that both acoustic and optical branches overall move downward from As to SbAs to Sb monolayer, and the widthes of acoustic and optical branches gradually become narrow.…”
Section: Main Calculated Results and Analysismentioning
confidence: 91%
“…In theory, thermal transports of lots of 2D materials have been widely investigated by semiclassical Boltzmann transport theory, Green's function based transport techniques and equilibrium molecular dynamics simulations [8][9][10][11][12][13][14][15][16][17][18][19][20] . The thermal transports of group-VA elements (As, Sb, Bi) monolayers with buckled structure have been predicted [10][11][12] , and the lattice thermal conductivity from As to Bi monolayer monotonously decreases. It is reported that a buckled structure has three conflicting effects: increasing the Debye temperature, suppressing the acoustic-optical scattering and increasing the flexural phonon scattering.…”
Section: Introductionmentioning
confidence: 99%
“…The largest group velocity for ZA, TA and LA branches near Γ point is 0.58 kms −1 , 1.81 kms −1 and 2.60 kms −1 for SbTeI monolayer and 0.36 kms −1 , 1.58 kms −1 and 2.34 kms −1 for BiTeI monolayer. In other 2D materials, larger phonon group velocities near Γ point can be found than in ATeI (A=Sb, I) monolayers, such as in blue phosphorene, arsenene, antimonene, stanene and silicene 16,[18][19][20]24 . The small phonon group velocities can lead to lower thermal conductivity in ATeI (A=Sb, I) monolayers than in other 2D materials.…”
Section: Main Calculated Results and Analysismentioning
confidence: 99%
“…[33] for puckered arsenene by first-principles calculations and Boltzmann transport theory, demonstrating high anisotropy. The same approach applied to buckled antimonene yields, at 300 K, a low lattice thermal conductivity of 15.1 W m −1 K −1 [34], which can be further reduced by chemical functionalization [35]. The buckled and puckered structures of antimonene were also studied in Ref.…”
Section: Introductionmentioning
confidence: 99%